DIFUSI INOVASI PELAYANAN SEDINO MESTI DADI (SEMEDI) KABUPATEN SRAGEN - Anis Rizki Fadhilah; Retna a Hanani; Kismartini Kismartini (Journal of Public Policy and Management Review, 2023)
Sedino Mesti Dadi (SEMEDI) service innovation is an easy, cheap and fast population administration service. The SEMEDI innovation was successfully appointed as a national pilot innovation by the Indonesian Ministry of Home Affairs. The SEMEDI innovation at the Sragen Regency Population and Civil Registry Office is diffused and disseminated so that people receive and use services. The spread and adoption of innovation are factors that influence adopters in accepting/rejecting innovation. This study aims to describe and analyze the process of innovation diffusion and the factors that shape the diffusion of SEMEDI service innovations. This study uses a qualitative descriptive research method. Data collection techniques used are interviews, documentation, and document studies. The results of the study show the history of the formation of SEMEDI innovation due to the practice of brokering in administrative services. The innovation diffusion process is analyzed through 4 elements, namely innovation, communication channels, time period, and social system. SEMEDI's innovation has met the characteristics of innovation. Communication channels used in spreading SEMEDI innovations are interpersonal communication and mass media. SEMEDI's innovation goes through 4 stages of innovation decisions, namely the knowledge stage, the decision-making stage, the implementation stage, and the confirmation stage. The types of SEMEDI innovation adopters are innovators (innovators) are heads of departments and heads of departments, early adopters are section heads, the early majority are employees, the late majority are visitors to Disdukcapil Sragen Regency, and groups kolot (laggard) is Calo. SEMEDI's innovation diffusion process is supported by forming factors that support the spread of innovation in a sustainable manner, namely Knowledge of Innovation and Reinvention factors, External Accountability factors, and Organizational Structure factors.